Fiqh and Sufistic Tafsir of the Quranic Verses on Interreligious Interaction in Indonesia - Syarif Syarif; Saifuddin Herlambang; Abdel Kadir Naffati (Al-Hayat: Journal of Islamic Education, 2022)
This research focuses on formulating how religious groups in Indonesia interact about differences in interpretation between the two schools of fiqh and Sufism. To examine the differences between the two schools of thought, a comparative method (muqâranat) is used, which analyzes how each school of thought interprets verses that discuss relationships between different religions. This research uses a thematic (maudlâ'î) and analytical (tahlîlî) approach in its investigation. Data sources were obtained from interpretations of the Qur'an and hadith related to school and community relations management. The variations used include those representing the Maliki school of thought: al-Jâmi' li Ahkâm al-Qur'ân by al-Qurthûbî and Ahkâm al-Qur'ân by Ibn al-'Arab. As for representing the interpretation of fiqh among the Hanafi school of thought, Ahkâm al-Qur'ân by al-Jashshâsh. Data analysis was done on two arrangements by contrasting the two interpretation patterns in interpreting verses about interactions between religious communities. The findings of this research show that in the interpretation of fiqh, the performance of poems related to forms of interaction between religious communities tends to be exclusive and discriminatory. The findings of this research support the opinion of Abdulaziz Sachedina and Abd. Muqsith Ghazali believes that fiqh scholars are responsible for implementing the law.